2015
DOI: 10.1007/s11883-015-0539-0
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I-Directed Therapies for the Management of Atherosclerosis

Abstract: Several recent reports have raised doubts about the atheroprotective role of high-density lipoprotein cholesterol (HDL-C). Nevertheless, a substantial body of work supports the validity of pharmacological interventions able to enhance HDL function, as opposed to raising HDL-C levels per se. In this article, we briefly review the development of pharmacological interventions that target apoA-I and HDL function as a means of reducing atherosclerotic risk: small molecule pharmaceuticals, small HDL mimetic peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Because of the central role of apo A-I in mediating cholesterol efflux, several groups have developed therapies aimed at increasing plasma apo A-I levels or augmenting plasma apo A-I-like activity. These therapies, which include small molecules that increase apo A-I synthesis, apo A-I-mimetic peptides, and infusion of apo A-I protein, 17 have yielded promising results in animals and in small clinical trials. 13, 42, 43 However, none has shown benefit in a large human trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the central role of apo A-I in mediating cholesterol efflux, several groups have developed therapies aimed at increasing plasma apo A-I levels or augmenting plasma apo A-I-like activity. These therapies, which include small molecules that increase apo A-I synthesis, apo A-I-mimetic peptides, and infusion of apo A-I protein, 17 have yielded promising results in animals and in small clinical trials. 13, 42, 43 However, none has shown benefit in a large human trial.…”
Section: Discussionmentioning
confidence: 99%
“…9-11 Related therapeutic approaches include efforts to increase plasma levels of apolipoprotein (apo) A-I (the most abundant protein in HDL-C) 12 by: 1) infusion of apo A-I protein, complexed with lipid to extend plasma half-life; 2) delivery of small molecules that mimic the function of apo A-I; or 3) use of drugs that enhance the function of plasma HDL. These approaches have shown promise in animal models and small human trials, 13-17 but have not yet shown clinical benefit in larger human trials. 18-20 Moreover, lifetime injections of apo A-I protein or apo A-I-mimetic peptides would be both expensive and impractical.…”
mentioning
confidence: 99%
“…Targeting Foam Cells by Natural Products that were well described in several reviews (Millar and Cuchel, 2015;Stoekenbroek et al, 2015). The ApoA-1mimetic peptides (e.g., 4F, 6F, FX-5A, ATI-5261, and ETC-642) (Garber et al, 1992;Wool et al, 2008;Stoekenbroek et al, 2015) and modified ApoA-1 (Graversen et al, 2008) strongly induced the macrophage cholesterol efflux and exhibited antiatherogenic properties.…”
Section: Macrophage Cholesterol Effluxmentioning
confidence: 99%
“…Some studies have also indicated that infusion with rHDL can influence apoAI concentrations and lipidome profiles of native HDL ( Nanjee et al, 1999 ); increase the concentrations of preβ-1 HDL ( Nanjee et al, 2001 ) and improve anti-inflammatory function of native HDL ( Patel et al, 2009 ). More detailed information on the apoAI-directed therapies can be found in the review ( Millar and Cuchel, 2015 ).…”
Section: Novel Therapy To Target Protective Hdl Subclassmentioning
confidence: 99%